Effects of Exercise Training under Hyperbaric Oxygen on Oxidative Stress Markers and Endurance Performance in Young Soccer Players: A Pilot Study - Carlos Burgos; Carlos Henríquez-Olguín; David Cristóbal Andrade; Rodrigo Ramírez-Campillo; Oscar F. Araneda; Allan White; Hugo Cerda-Kohler (Journal of Nutrition and Metabolism)
The aim of the present study was to determine the effects of three weeks of hyperbaric oxygen (HBO2) training on oxidative stress markers and endurance performance in young soccer players. Participants (18.6±1.6 years) were randomized into hyperbaric-hyperoxic (HH) training (n=6) and normobaric normoxic (NN) training (n=6) groups. Immediately before and after the 5th, 10th, and 15th training sessions, plasma oxidative stress markers (lipid hydroperoxides and uric acid), plasma antioxidant capacity (6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid [TROLOX]), arterial blood gases, acid-base balance, bases excess (BE), and blood lactate analyses were performed. Before and after intervention, maximal oxygen uptake (VO2max) and peak power output (PPO) were determined. Neither HH nor NN experienced significant changes on oxidative stress markers or antioxidant capacity during intervention. VO2max and PPO were improved (moderate effect size) after HH training. The results suggest that HBO2 endurance training does not increase oxidative stress markers and improves endurance performance in young soccer players. Our findings warrant future investigation to corroborate that HBO2 endurance training could be a potential training approach for highly competitive young soccer players.